Determinasi Perlekatan dan Posisi Ibu Menyusui dalam Memberikan ASI terhadap Keberhasilan Pemberian ASI Eksklusif di Wilayah Kerja Puskesmas Oesapa - Putri Kencana Jafrizal; Utma Aspatria; Marselinus Laga Nur (Yayasan Literasi Sains Indonesia, 2024)
Insufficient breastfeeding can cause malnutrition babies, making them more susceptible disease. Breastfeeding baby for 6 months without additional food, drink is called exclusive breastfeeding. Improper breastfeeding position and attachment can result in low breast milk production. Apart from making the nipples feel sore and causing breast milk not to come out optimally, incorrect breastfeeding techniques can also make the baby refuse to breastfeed, which has a negative impact on breast milk production. The aim of research determine the influence of the position and attachment of breastfeeding mothers and their role on the effectiveness of exclusive breastfeeding in the Oesapa Community Health Center working area. The research design is case control which is used together with observational analysis as research methodology. Complete sampling and significance threshold of α=0.05, 27 case samples and 27 control samples. This study, data were analyzed using methods, univariate, bivariate (chi square statistical test to assess the influence position and attachment style of breastfeeding mothers on the success of exclusive breastfeeding in the Oesapa Community Health Center), multivariate (logistic regression). statistical test to identify the most dominant variable). attachment and body posture in relation to effectiveness of exclusive breastfeeding. The results of the study showed that there was relationship between attachment (p-value= 0.000, OR=9.534), position (p-value 0.000, OR=12.025) and the success of exclusive breastfeeding. Recommended that health workers facilitate and motivate the implementation of breastfeeding, especially exclusive breastfeeding, to their citizens, increase the role of health workers educating breastfeeding mothers to apply the correct latch and position.